Adoptive cell therapy for high grade gliomas using simultaneous temozolomide and intracranial mgmt-modified γδ t cells following standard post-resection chemotherapy and radiotherapy: current strategy and future directions - Nabors, L. B.; Lamb, L. S.; Goswami, T.; Rochlin, K.; Youngblood, S. L. (Frontiers in Immunology, 2024)
Cellular therapies, including chimeric antigen receptor T cell therapies (CAR-T), while generally successful in hematologic malignancies, face substantial challenges against solid tumors such as glioblastoma (GBM) due to rapid growth, antigen heterogeneity, and inadequate depth of response to cytoreductive and immune therapies, We have previously shown that GBM constitutively express stress associated NKG2D ligands (NKG2DL) recognized by gamma delta (γδ) T cells, a minor lymphocyte subset that innately recognize target molecules via the γδ T cell receptor (TCR), NKG2D, and multiple other mechanisms. Given that NKG2DL expression is often insufficient on GBM cells to elicit a meaningful response to γδ T cell immunotherapy, we then demonstrated that NKG2DL expression can be transiently upregulated by activation of the DNA damage response (DDR) pathway using alkylating agents such as Temozolomide (TMZ). TMZ, however, is also toxic to γδ T cells. Using a p140K/MGMT lentivector, which confers resistance to TMZ by expression of O(6)-methylguanine-DNA-methyltransferase (MGMT), we genetically engineered γδ T cells that maintain full effector function in the presence of therapeutic doses of TMZ. We then validated a therapeutic system that we termed Drug Resistance Immunotherapy (DRI) that combines a standard regimen of TMZ concomitantly with simultaneous intracranial infusion of TMZ-resistant γδ T cells in a first-in-human Phase I clinical trial (NCT04165941). This manuscript will discuss DRI as a rational therapeutic approach to newly diagnosed GBM and the importance of repeated administration of DRI in combination with the standard-of-care Stupp regimen in patients with stable minimal residual disease.